Single-stage debridement and spinal fusion using PEEK cages through a posterior approach for eradication of lumbar pyogenic spondylodiscitis: a safe treatment strategy for a detrimental condition. Issue 1 (December 2015) - Tschöke, Sven; Fuchs, Holger; Schmidt, Oliver; Gulow, Jens; von der Hoeh, Nicolas; Heyde, Christoph-E.
Abstract Background Pyogenic infections of the lumbar spine are a rare but critical pathology, yet with considerably high mortality rates. In cases indicating surgical therapy, the implantation of titanium cages or autologous bone grafts represent today's gold standard. Although non-metallic implants such as poly-ether-ether-ketone (PEEK) have proven to be advantageous in diverse degenerative conditions, their saftey and practicability in lumbar spine infection remains questionable. Moreover, the efficacy of a single-step radical debridement of the infected disc space with subsequent fusion from a strictly posterior approach continues to be an issue of debate. We therefore sought to evaluate the feasibility, clinical and radiological outcome of a single-step TLIF procedure using oblique PEEK cages in the surgical management of patients with lumbar pyogenic spondylodiscitis. Methods From January 2009 through December 2013, all patients meeting the indication for surgical treatment of lumbar pyogenic spondylodiscitis were included. Patients demonstrating intact cortical bone on preoperative CT received a single-step radical debridement of the infected intervertebral disc space, posterior screw-and-rod instrumentation and implantation of an oblique PEEK cage using the TLIF technique. Oral antibiotics were continued for 12 weeks postoperatively and clinical and radiological results recorded throughout a minimum 1-year clinical follow-up. Results A total of 104 patients were admitted to receive surgical therapy for lumbar pyogenic spondylodiscitis. Within this patient population, 18 patients met the diagnostic criteria to receive the implantation of an oblique PEEK cage. Pathogens were detected in 13 cases with Staph. aureus being the predominant causative organism. All patients were discharged to recover in their domestic environment. Throughout the first year of clinical and radiological follow-up and beyond, none of the 18 patients demonstrated any signs of residual neurologic deficits or recurrent infection. Furthermore, two-plane conventional X-rays showed no significant implant subsidence or failure at any of the given time-points in up to 5 years postoperatively. Conclusions In patients meeting the criteria for surgical treatment of lumbar pyogenic spondylodiscitis, the implantation of PEEK cages using a single-step TLIF approach is a safe and feasible procedure. Based on our experience, the concern of a recurrent infection when implanting non-metallic cages may be refuted in carefully selected patients.